Pengaruh Real Earnings Management dan Audit Tenure Terhadap Kualitas Audit - Rachmawati, Citra; Triani, Ni Nyoman Alit (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the effect of real earnings management and audit tenure on audit quality, as measured by audit fees, in energy sector companies listed on the Indonesia Stock Exchange. The study employed a quantitative approach, utilizing secondary data obtained through documentation techniques on the companies' annual reports and financial statements. The research sample was determined using a purposive sampling technique, resulting in 130 company observations that met the research criteria. Data analysis was conducted using multiple linear regression to test the effect of each independent variable on audit fees. The results showed that real earnings management had a positive effect on audit fees, indicating that the practice of manipulating real earnings increases audit complexity and risk, requiring auditors to undertake greater audit efforts. Furthermore, audit tenure also affected audit fees, indicating that the length of the working relationship between the auditor and the client influences the agreed-upon audit fee. These findings imply that company characteristics and the auditor-client relationship need to be taken into account when determining audit fees and can be considered by auditors, companies, and regulators in maintaining the quality of the audit process.